2009
DOI: 10.1063/1.3122007
|View full text |Cite
|
Sign up to set email alerts
|

Image formation, resolution, and height measurement in scanning ion conductance microscopy

Abstract: Scanning ion conductance microscopy ͑SICM͒ is an emerging tool for the noncontact investigation of biological samples such as live cells. It uses an ion current through the opening of a tapered nanopipette filled with an electrolyte for topography measurements. Despite its successful application to numerous systems no systematic investigation of the image formation process has yet been performed. Here, we use finite element modeling to investigate how the scanning ion conductance microscope images small partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
131
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 19 publications
(22 reference statements)
12
131
0
Order By: Relevance
“…We showed that the lateral resolution of the ARS/hopping SICM mode is about 50 nm, which is comparable to the finding by previous investigators (Novak et al, 2009;Happel and Dietzel, 2009). However, the actual resolution of SICM imaging is still a matter of debate (Rheinlaender and Schaffer, 2009). Theoretical studies of SICM will be required to consider the resolution in relation to the pipette radius and other parameters, although there are a few papers already in this field (Edwards et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…We showed that the lateral resolution of the ARS/hopping SICM mode is about 50 nm, which is comparable to the finding by previous investigators (Novak et al, 2009;Happel and Dietzel, 2009). However, the actual resolution of SICM imaging is still a matter of debate (Rheinlaender and Schaffer, 2009). Theoretical studies of SICM will be required to consider the resolution in relation to the pipette radius and other parameters, although there are a few papers already in this field (Edwards et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…3 A and B, Lower) further show that the membrane is predominately flat in the center of the pore. Of note is that no detailed information about the precise membrane curvature at the pore rims can be extracted, due the finite lateral resolution (∼100 nm to 200 nm, depending on the size of the aperture) of the SICM method (38,39).…”
Section: Resultsmentioning
confidence: 99%
“…Method 1 assumes that the ratio between the outer and inner diameter of a nanopipette remains constant to that at the nanopipette opening, 13,41,52 and, as such, the inner nanopipette angle can be calculated by using the relationship:…”
Section: Evaluation Of Existing Methods For Nanopipette Characterizationmentioning
confidence: 99%